2014
DOI: 10.1111/ejss.12154
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition impacts on the amount and stability of soil organic matter in an alpine meadow ecosystem depend on the form and rate of applied nitrogen

Abstract: Summary The effects of atmospheric nitrogen (N) deposition on carbon (C) sequestration in terrestrial ecosystems are controversial. Therefore, it is important to evaluate accurately the effects of applied N levels and forms on the amount and stability of soil organic carbon (SOC) in terrestrial ecosystems. In this study, a multi‐form, small‐input N addition experiment was conducted at the Haibei Alpine Meadow Ecosystem Research Station from 2007 to 2011. Three N fertilizers, NH4Cl, (NH4)2SO4 and KNO3, were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…At each plot, the litter layer was removed and mineral soil at depths of 0-15 cm was collected. Five soils from two diagonal lines through each plot were collected and pooled to one composite sample (Fang et al 2014c). Soils were sieved to 2-mmmesh size and then transported to the laboratory in a chilled polystyrene box.…”
Section: Soil Sampling and Plfa Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…At each plot, the litter layer was removed and mineral soil at depths of 0-15 cm was collected. Five soils from two diagonal lines through each plot were collected and pooled to one composite sample (Fang et al 2014c). Soils were sieved to 2-mmmesh size and then transported to the laboratory in a chilled polystyrene box.…”
Section: Soil Sampling and Plfa Measurementmentioning
confidence: 99%
“…At the later stage of N saturation, inorganic N accumulation in soils inhibits the activity of white rot fungi and extracellular enzyme synthesis, thereby reduces litter decay and soil CO 2 emission (Zak et al 2011). The N input rate at the transition point when N input stimulates soil organic matter decomposition changes to suppress soil organic matter decomposition is defined as N critical load (Fang et al 2014c). For a special ecosystem, however, the critical load of N deposition for the alteration of soil CO 2 emission is not well estimated.…”
Section: Introductionmentioning
confidence: 99%
“…N deposition is a component of global change that has a considerable impact on belowground carbon dynamics and has become a hotspot for research on the ecosystem's carbon cycle. Some studies have found that N addition increases the soil organic carbon (SOC) pool [10], but other studies have shown that N addition can aggravate SOC loss [11,12]. The different results depend on the different ecosystems, the level of N application, and the duration of N application.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to improve the method of static chambers and gas chromatography for soil N 2 O emission measurement, scientists of ChinaFLUX conducted systematic comparative experiments in aspects of static chambers construction, sampling plots setup, sampling frequency, and instruments (Zheng et al, 2008). Nowadays, the findings have formed a series of operational procedure and been widely used by many scientists (Zheng et al, 2008;Fang et al, 2014aFang et al, , 2014b.…”
Section: Design Of the Coordinated Observation On Terrestrial Ecosystmentioning
confidence: 99%